Inhibitors Targeting Multiple Janus Kinases From Zanthoxylum simulans Mediate Inhibition and Apoptosis Against Gastric Cancer Cells via the Estrogen Pathway - Tian, Yong-Qiang; Hu, Dai; Zhang, Yong-Li; Zou, Jian; Chen, Gui-Lin; Guo, Ming-Quan (Frontiers in Chemistry, 2022)
Janus kinases (JAKs) play a key role in subtly regulating proliferation, apoptosis and differentiation of cancer cells, and their inhibitors are actively sought as new drug leads. By developing JAKs based affinity ultrafiltration method coupled with LC/Q-TOF-MS in order to discover selective JAKs inhibitors from total quaternary alkaloids (QAs) from Zanthoxylum simulans, peak 19 (Berberine) and peak 21 (Chelerythrine) were revealed to exhibit notable selectivity on JAK1, JAK2 and JAK3 over Tyk2. In addition, Chelerythrine showed stronger inhibitory activity than positive control (Cerdulatinib) on gastric cancer cells (AGS), while Berberine with weaker inhibition. Further molecular docking analysis revealed their discrepancies due to different interaction bonds and characteristic residues. Quaternary N was proposed as the functional group to enhance the selectivity to JAK1, and some specific moieties towards Asp1021, Leu855 and Leu828 were suggested to increase the selectivity for JAK1, JAK2 and JAK3, respectively. As the most potential inhibitor of JAKs from QAs, Chelerythrine exhibited distinct suppression on adhesion, migration, invasion and stimulating apoptosis of AGS cells, which was consistent with the significant down-regulation of estrogen receptors (ER-α36, ER-α66 and ER-β1) and Src expression. In conclusion, an efficient screening approach was developed to identify Berberine and Chelerythrine as potential selective candidates from Zanthoxylum simulans with significant anti-proliferative activity against gastric carcinoma. As we know, it was the first report to propose estrogen signal pathway for Chelerythrine in anti-gastric cancer cells (AGS) study. The results supported Chelerythrine inhibitory effects on AGS by not only direct inhibiting JAKs but also down-regulating estrogen pathway.